Clinical effect of quadrant-wise non-surgical periodontal treatment on patients with stage III grade B and C periodontitis - YILDIRIM, HATİCE SELİN (My University, 2023)
Objective: The aim of this study was to evaluate clinical effects of quadrant-wise non-surgical periodontal treatment in patients with stage-III grade-B and grade-C periodontitis. Methods: Forty-five non-smoker individuals who were systemically healthy, including 15 peri-odontally healthy, 15 stage-III grade-B periodontitis participant, and 15 stage-III grade-C peri-odontitis participant, were involved in this study. At baseline, plaque index, gingival index, probing depth, clinical attachment level, and bleeding on probing were evaluated for all participants, and in periodontitis groups, probing depth measurements were categorized as intermediate (4-6 mm) and deep (>6 mm), and the percentages of all categorized probing depths were calcu-lated. Quadrant-wise non-surgical periodontal treatment was performed in both periodontitis groups, and clinical measurements were performed again 1 and 3 months after quadrant-wise non-surgical periodontal treatment. Results: At baseline, periodontitis was higher in stage-III grade-C group than stage-III grade-B group (P .05). All clinical parameters improved from baseline to 1 and 3 months in all periodontitis groups (P >.05). The reduction of percentage of the regions with probing depth of 4-6 mm from baseline to 3 months was higher in stage-III grade-B group than stage-III grade-C group (P <.05). As compared to the stage-III grade-B group at 1 and 3 months, the percentage of sites with probing depth ≥ 5 mm and BOP+(%) was higher in the stage-III grade-C group (P <.05). Conclusion: According to residual probing depth and deep periodontal pockets, the clinical response of quadrant-wise non-surgical periodontal treatment was superior in stage-III grade-B periodontitis group than stage-III grade-C periodontitis group, and there was a need for periodontal surgical treatment after quadrant-wise non-surgical periodontal treatment in the stage-III grade-C periodontitis group.
Kadran bazlı cerrahi olmayan periodontal tedavinin evre III Derece B ve derece C periodontitis hastalarındaki klinik etkisi
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Diş Hekimliği (çeşitli); Dentistry (miscellaneous); Dental scaling; periodontitis; root planing